Quality Assessment and Physicochemical Characteristics of Bran Enriched Chapattis - B. N. Dar; Savita Sharma; Baljit Singh; Gurkirat Kaur (International Journal of Food Science)
Cereal brans singly and in combination were blended at varying levels (5 and 10%) for development of Chapattis. Cereal bran enriched Chapattis were assessed for quality and physicochemical characteristics. On the basis of quality assessment, 10% enrichment level for Chapatti was the best. Moisture content, water activity, and free fatty acids remained stable during the study period. Quality assessment and physicochemical characteristics of bran enriched Chapattis carried out revealed that dough handling and puffing of bran enriched Chapattis prepared by 5 and 10% level of bran supplementation did not vary significantly. All types of bran enriched Chapattis except rice bran enriched Chapattis showed nonsticky behavior during dough handling. Bran enriched Chapattis exhibited full puffing character during preparation. The sensory attributes showed that both 5 and 10% bran supplemented Chapattis were acceptable.